Plywoods of northeast Argentinian woods and soybean protein-based adhesives: Relationship between morphological aspects of veneers and shear strength values - Nicolao, Erika Susana (2021)
Three-ply plywoods were produced using pine and Eucalyptus northeast Argentinian woods. A no-added formaldehyde biobased-adhesive was used for assembly, based on chemically modified soy protein concentrate. In this work we focused on the relationship between bonding quality parameters of the plywoods and the morphology of the glued line. Wood characteristics such as contact angle, roughness, density and moisture content were measured prior to plywood assembly. Bonding quality parameters (percentage ofwood failure and shear strength) of the plywood were measured according to Argentinean standard IRAM 9562 and the results were evaluated with respect to microscopic observations of the glue joint. Eucalyptus wood was suitable for plywood interiorcondition applications, while pine barely exceeded the standards imposed by the norm.